Methodologies for Seismic Soil-Structure Interaction Analysis in the Design and Assessment of Nuclear Installations - IAEA (IAEA, 2022)
Presents soil-structure interaction (SSI) phenomena and current practices in SSI modelling, simulation methodology and analysis methods for the design and assessment of nuclear installations.
Description based upon print version of record.
Keywords: Earthquake hazard analysis.; elektronické knihy; electronic books